1982
DOI: 10.2105/ajph.72.11.1251
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in fatal poisoning by opiates in the United States.

Abstract: For all ages combined, 63 per cent of fatal unintentional poisonings from solids and liquids involve drugs, licit and illicit. In 1978, 1,906 deaths in the United States were ascribed to unintentional poisoning by drugs.2 An observation that such deaths had declined sharply since 1975 led us to review published mortality data for the 1970s. Our preliminary study suggested intriguing similarities between epidemiologic trends in unintentional drug poisoning from 1970-1978* and trends in acute narcotism deaths in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Although the earliest epidemics of fatal drug overdoses in the United States were associated with prescription drugs, 1 most drug overdoses since the 1970s have been a consequence of the abuse of illicit drugs such as heroin. 2,3 Most of the scientific knowledge about drug overdose epidemics in the United States has therefore come from studies of illicit drug use in urban populations. 1,[4][5][6][7] Recent reports, however, indicate that the misuse and abuse of prescription drugs may have once again become more common than illicit drug poisoning in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Although the earliest epidemics of fatal drug overdoses in the United States were associated with prescription drugs, 1 most drug overdoses since the 1970s have been a consequence of the abuse of illicit drugs such as heroin. 2,3 Most of the scientific knowledge about drug overdose epidemics in the United States has therefore come from studies of illicit drug use in urban populations. 1,[4][5][6][7] Recent reports, however, indicate that the misuse and abuse of prescription drugs may have once again become more common than illicit drug poisoning in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Opiate dependence is associated with significant morbidity and mortality[1–4], much of which is reduced by methadone maintenance [5–9]. One form of morbidity that has been clearly demonstrated in heroin users is disruption of menstrual function [10–12].…”
Section: Introductionmentioning
confidence: 99%
“…A MEDLINE search of the terms ‘methadone’ and ‘menstruation’ from 1969 to 2003 yielded only eight references. Some studies have shown little or no improvement [11–12], while others report definite improvement [1,3–14]. Furthermore, there is little published on whether other factors such as age, race, concurrent cocaine use or weight could contribute to menstrual cycles of maintained women.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, direct measures of drug use are not available for the time period of my study. The best indirect measure of over‐time drug use is the annual drug mortality rate (Paulozzi and Xi ; Samkoff and Baker ), which assumes that an increase in drug‐related deaths coincides with increased drug use. I employ this proxy to control for Drug Use .…”
Section: Data and Analysismentioning
confidence: 99%